Multiple episodes of extensive marine anoxia linked to global warming and continental weathering following the latest Permian mass extinction - Zhang, Feifei (Sci Adv, 2018)
Explaining the ~5-million-year delay in marine biotic recovery following the latest Permian mass extinction, the largest biotic crisis of the Phanerozoic, is a fundamental challenge for both geological and biological sciences. Ocean redox perturbations may have played a critical role in this delayed recovery. However, the lack of quantitative constraints on the details of Early Triassic oceanic anoxia (for example, time, duration, and extent) leaves the links between oceanic conditions and the delayed biotic recovery ambiguous. We report high-resolution U-isotope (δ(238)U) data from carbonates of the uppermost Permian to lowermost Middle Triassic Zal section (Iran) to characterize the timing and global extent of ocean redox variation during the Early Triassic. Our δ(238)U record reveals multiple negative shifts during the Early Triassic. Isotope mass-balance modeling suggests that the global area of anoxic seafloor expanded substantially in the Early Triassic, peaking during the latest Permian to mid-Griesbachian, the late Griesbachian to mid-Dienerian, the Smithian-Spathian transition, and the Early/Middle Triassic transition. Comparisons of the U-, C-, and Sr-isotope records with a modeled seawater PO(4)(3−) concentration curve for the Early Triassic suggest that elevated marine productivity and enhanced oceanic stratification were likely the immediate causes of expanded oceanic anoxia. The patterns of redox variation documented by the U-isotope record show a good first-order correspondence to peaks in ammonoid extinctions during the Early Triassic. Our results indicate that multiple oscillations in oceanic anoxia modulated the recovery of marine ecosystems following the latest Permian mass extinction.